Differences in Carcinogenic Risk Factors for Histopathological Types of Nasopharyngeal Malignancies Based on WHO Classification - Gabriela Gusti; Hendrianto Hendrianto (Journal of Social Research, 2025)
Nasopharyngeal carcinoma (NPC) remains a major malignancy in Southeast Asia, including Indonesia. Variations in histopathological types are suspected to be influenced by carcinogenic risk factors such as smoking, consumption of grilled foods, preserved foods, and alcohol intake. This study aims to analyze differences in the dominant histopathological types of NPC—Keratinizing Squamous Cell Carcinoma (KSCC), Non-Keratinizing Squamous Cell Carcinoma (NKSCC), and Undifferentiated Cell Carcinoma—based on major risk factors in Medan. An analytical observational study with a cross-sectional design was conducted using 75 eligible medical records of NPC patients (2020–2025) from Royal Prima Ayahanda Hospital Medan and Dr. Pirngadi General Hospital Medan. Data were analyzed using Chi-Square or Fisher’s Exact Test and Odds Ratio. Results indicate that Undifferentiated Cell Carcinoma is the most prevalent type (61.3%), followed by NKSCC (29.3%) and KSCC (9.3%). No significant association was found between smoking, grilled food consumption, preserved food intake, or alcohol use and the histopathological types (p > 0.05). However, a higher risk tendency was observed for preserved food consumption toward KSCC (OR = 6.00) and grilled food consumption toward KSCC (OR = 2.98). These findings provide preliminary insight into how carcinogenic exposures may shape histopathological patterns of NPC and support future prevention and screening strategies in endemic regions.